(untitled) (Journal of the College of Basic Education, 2022)
The current study, tagged (the visual image and its social impact in its creation), is based on three chapters. The first chapter included the methodological framework for the research from the research problem, its importance, and the desired goal to be achieved, with a definition of the most important topics that originate in the title of the research, with a procedural definition for each inclusion. The chapter included the mechanism that it followed. The researcher aims to achieve this by monitoring the impact of the image on the child’s upbringing, according to the observation and analysis list survey.